Characteristics of effective Assatizah in Higher Religious Institutions (HRIs) - Yusoff, Husnina; Anuar, Ashraff; Asmuni, Azizan; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2018)
With the increase numbers of students registered in Tahfiz Higher Religious Institutions (HRIs) to pursue their Degree Diploma, shows that in recent years, studies in the field of Quranic are getting more encouraging response from communities. The need for professional Assatizah is so important in Islam as well among the community. Thus, it is important to study the quality of Assatizah in order to generate high qualities graduates from HRIs. Characteristics of teacher can be defined as qualities that is measurable with evaluation or their professional records. This paper is unique because the authors are investigate what qualities Assatizah need to produce high qualities graduates from HRIs. This paper highlighting specific characteristics that Assatizah need to have due to their tasks and responsibilities as an Assatizah. Assatizah must have certain specific attributes so that they can designate their role as a good Assatizah and inherit the Rasul duties. To become a professional Assatizah, they need to have knowledge, skills to teach and display positive personalities. They need to have knowledge in a) subject matters, b) knowledge in teaching; skills in a) teaching b) communication skills c) classroom management skills; affective outcomes a) self-efficacy b) professionalism. A future research would discover more variables that be related in teacher characteristics in Assatizah. Another area would be teacher competencies in teaching in HRIs. Continued studies in teacher characteristic can contribute to the institute to improve job performance among Assatizah in teaching. New theories or model in job performance can open new dimension of research.